2012
DOI: 10.1182/blood-2012-05-433946
|View full text |Cite
|
Sign up to set email alerts
|

Shared monocyte subset phenotypes in HIV-1 infection and in uninfected subjects with acute coronary syndrome

Abstract: The mechanisms responsible for increased cardiovascular risk associated with HIV-1 infection are incompletely defined. Using flow cytometry, in the present study, we examined activation phenotypes of monocyte subpopulations in patients with HIV-1 infection or acute coronary syndrome to find common cellular profiles. Nonclassic (CD14+CD16++) and intermediate (CD14++CD16+) monocytes are proportionally increased and express high levels of tissue factor and CD62P in HIV-1 infection. These proportions are related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
231
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(250 citation statements)
references
References 55 publications
16
231
2
Order By: Relevance
“…This was the first report of the monocyte subset distribution in primary HIV-1 infection, and it expanded previous observations that had focused on chronic HIV-1-infected patients, HARRT patients, and elite controllers. 16,17,30 In contrast to the report by Han et al, 16 we found that CD14 dim CD16 1 and CD14 high CD16 2 monocytes were negatively correlated with CD4 counts in PHI but not CHI. This difference might be due to our limited case numbers in the CHI group.…”
Section: Monocyte Subset Frequencies Are Altered During Hiv-1 Infectioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This was the first report of the monocyte subset distribution in primary HIV-1 infection, and it expanded previous observations that had focused on chronic HIV-1-infected patients, HARRT patients, and elite controllers. 16,17,30 In contrast to the report by Han et al, 16 we found that CD14 dim CD16 1 and CD14 high CD16 2 monocytes were negatively correlated with CD4 counts in PHI but not CHI. This difference might be due to our limited case numbers in the CHI group.…”
Section: Monocyte Subset Frequencies Are Altered During Hiv-1 Infectioncontrasting
confidence: 56%
“…[22][23][24] Increased immune activation of monocytes was reported to be involved in HIV-1 pathogenesis and thus associated with CVD risk. 17,28,29 In the present study, we demonstrated that in contrast to the decreased percentage of CD14 high CD16 2 monocyte subset, CD14 dim CD16 1 and CD14 high CD16 1 monocyte subsets were expanded during both primary and chronic HIV-1 infection. This was the first report of the monocyte subset distribution in primary HIV-1 infection, and it expanded previous observations that had focused on chronic HIV-1-infected patients, HARRT patients, and elite controllers.…”
Section: Monocyte Subset Frequencies Are Altered During Hiv-1 Infectionmentioning
confidence: 70%
See 1 more Smart Citation
“…7A, 7B), indicating that monocytes from HIV patients are in a heightened activation state perhaps owing to persistent viral replication, exposure to homeostatic cytokines, and to microbial products (33)(34)(35). Furthermore, to directly examine the immunosuppressive role of LY6E in HIV infection, CD14…”
Section: Ly6e Represses the Responsiveness Of Primary Monocytes To Lpmentioning
confidence: 99%
“…Of these comorbidities, the management of CAD has been a point of emphasis. Infection with HIV leads to dysregulation of the immune system resulting in immune hyperactivation 5,6 and a systemic ''cytokine storm.'' 7 Furthermore, coronary atherosclerotic lesions in HIV-infected patients are often unstable and more prone to rupture, resulting in a 1.5-twofold higher incidence of acute coronary syndrome and myocardial infarction.…”
mentioning
confidence: 99%